ChemInform Abstract: A Titanium(III)‐Catalyzed Reductive Umpolung Reaction for the Synthesis of 1, 1‐Disubstituted Tetrahydroisoquinolines. Issue 37 (September 2015) - Luu, Hieu‐Trinh; Wiesler, Stefan; Frey, Georg; Streuff, Jan
Abstract A reductive C‐1 acylation of 3, 4‐dihydroisoquinolines is developed that gives selective access to 1, 1‐disubstituted tetrahydroisoquinolines via a Ti(III)‐catalyzed umpolung process.